2019
DOI: 10.3390/app9071462
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Deep Learning Neural Networks for Surface Roughness Prediction Using Vibration Signal Analysis

Abstract: The use of surface roughness (Ra) to indicate product quality in the milling process in an intelligent monitoring system applied in-process has been developing. From the considerations of convenient installation and cost-effectiveness, accelerator vibration signals combined with deep learning predictive models for predicting surface roughness is a potential tool. In this paper, three models, namely, Fast Fourier Transform-Deep Neural Networks (FFT-DNN), Fast Fourier Transform Long Short Term Memory Network (FF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 35 publications
0
51
0
Order By: Relevance
“…We next compared the proposed 1DCNFN with different models containing BPNN [8], ANFIS [10], FNN [11], and 1DCNN [21] to verify the prediction effectiveness. Here, the 1DCNN (used for comparison) has two convolutional layers, one pooling layer, and one fully connected layer; its architecture 1DCNN is detailed in Table VIII.…”
Section: B Surface Roughness Prediction Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next compared the proposed 1DCNFN with different models containing BPNN [8], ANFIS [10], FNN [11], and 1DCNN [21] to verify the prediction effectiveness. Here, the 1DCNN (used for comparison) has two convolutional layers, one pooling layer, and one fully connected layer; its architecture 1DCNN is detailed in Table VIII.…”
Section: B Surface Roughness Prediction Resultsmentioning
confidence: 99%
“…Step 3:Evaluate the fitness value of each particle by Eq. (21) and find out the personal best and global best .…”
Section: B Uag Parameter Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathew et al [16] showed that a tool wear span VB (mm), when milling EN-8 medium carbon steel, can be connected with the level of an acoustic emission expressed through a mean stress value AE (mV), while Lin et al [17] showed that it is possible to use ANNs for the surface roughness prediction based on a vibration signal when milling medium carbon steel S45C.…”
Section: Introductionmentioning
confidence: 99%
“…A deep learning network can self-learn the relevant features from multiple signals [21]. Deep learning algorithms are frequently used in areas such as bearing fault diagnosis [22], machine defect detection [23], vibration signal analysis [24], computer vision [25] and image classification [26]. Autoencoding is a process for nonlinear dimension reduction with natural transformation architecture using feedforward neural network [27].…”
Section: Introductionmentioning
confidence: 99%